PKM PENANAMAN NILAI KARAKTER DI TK DWP JANTI KECAMATAN TARIK SIDOARJO - SITI NURIYATIN; Risdiana Chandra Dhewy (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2018)
Devotion program (Pengabdian Kepada Masyarakat or PKM) aimed to describe implementation ofenvironmental care, honesty, and creative character in TK DWP Janti, Tarik, Sidoarjo. The development of the kinder gardens has not been fullestespecially if seen from the increase of numbers of students from year to year.This was happened because the limitation of the teacher competence development among kinder garden schools and kinder garden facilities that was not so good to support the learning proses.The subjects were the students and teacher of TK DWP Janti.The methods that were implemented in this PKM such as training and continuing education.The solutions that have been given in the activities of PKM were 1) a canteen honesty; 2) training instructional media from the used items as props as the embodiment of creative learning; 3) marketing training school through online media in the form of blogs.